Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
ISI Document Delivery No.: 705ZZ Times Cited: 117 Cited Reference Count: 55 Cited References: AUSTIN RH, 1975, BIOCHEMISTRY-US, V14, P5355, DOI 10.1021/bi00695a021 Birge RR, 1996, J PHYS CHEM-US, V100, P9990, DOI 10.1021/jp953669e BOUSCHE O, 1992, PHOTOCHEM PHOTOBIOL, V56, P1085, DOI 10.1111/j.1751-1097.1992.tb09732.x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BROOKS BR, 1995, J COMPUT CHEM, V16, P1522, DOI 10.1002/jcc.540161209 Brooks CL, 1988, PROTEINS THEORETICAL Brucherseifer M, 2000, APPL PHYS LETT, V77, P4049, DOI 10.1063/1.1332415 Chen Q, 2001, J OPT SOC AM B, V18, P823, DOI 10.1364/JOSAB.18.000823 DENCHER NA, 1989, P NATL ACAD SCI USA, V86, P7876, DOI 10.1073/pnas.86.20.7876 Der A, 2001, BIOCHEMISTRY-MOSCOW+, V66, P1234, DOI 10.1023/A:1013179101782 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 DOSTER W, 1989, NATURE, V337, P754, DOI 10.1038/337754a0 FERRAND M, 1993, P NATL ACAD SCI USA, V90, P9668, DOI 10.1073/pnas.90.20.9668 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRISCHKOWSKY D, 1991, OSA PROC, V9, P9 Guilbert C, 1996, CHEM PHYS, V204, P327, DOI 10.1016/0301-0104(95)00293-6 Han PY, 2000, OPT LETT, V25, P242, DOI 10.1364/OL.25.000242 Hinsen K, 1998, PROTEINS, V33, P417, DOI 10.1002/(SICI)1097-0134(19981115)33:3<417::AID-PROT10>3.0.CO;2-8 JANEZIC D, 1995, J COMPUT CHEM, V16, P1543, DOI 10.1002/jcc.540161210 Kusnetzow A, 1999, BIOPHYS J, V76, P2370, DOI 10.1016/S0006-3495(99)77394-7 Lanyi JK, 1999, INT REV CYTOL, V187, P161, DOI 10.1016/S0074-7696(08)62418-3 Lanyi JK, 2001, TRENDS BIOTECHNOL, V19, P140, DOI 10.1016/S0167-7799(01)01576-1 LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 LONGBOTTOM C, 2002, POTENTIAL USES TERAH Luecke H, 1999, SCIENCE, V286, P255, DOI 10.1126/science.286.5438.255 Luecke H, 1999, J MOL BIOL, V291, P899, DOI 10.1006/jmbi.1999.3027 MacKerell AD, 1998, J PHYS CHEM B, V102, P3586, DOI 10.1021/jp973084f Markelz AG, 2000, CHEM PHYS LETT, V320, P42, DOI 10.1016/S0009-2614(00)00227-X MCINTOSH AR, 1991, BIOPHYS J, V60, P1, DOI 10.1016/S0006-3495(91)82025-2 MOUAWAD L, 1993, BIOPOLYMERS, V33, P599, DOI 10.1002/bip.360330409 Mouawad L, 1996, J MOL BIOL, V258, P393, DOI 10.1006/jmbi.1996.0257 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Oesterhelt D, 1974, Methods Enzymol, V31, P667 Palmo K, 1998, J COMPUT CHEM, V19, P754, DOI 10.1002/(SICI)1096-987X(199805)19:7<754::AID-JCC6>3.0.CO;2-P PERAHIA D, 1995, COMPUT CHEM, V19, P241, DOI 10.1016/0097-8485(95)00011-G Person W.B., 1982, VIBRATIONAL INTENSIT Polavarapu P. L., 1998, VIBRATIONAL SPECTRA POWELL JW, 1991, J MOL STRUCT, V247, P107, DOI 10.1016/0022-2860(91)87067-R POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 Ren L, 2001, BIOCHEMISTRY-US, V40, P13906, DOI 10.1021/bi0116487 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 Sass HJ, 1997, EMBO J, V16, P1484, DOI 10.1093/emboj/16.7.1484 Stuart JA, 1996, BIOMEMBR A&B, V2, P33 Urabe H, 1998, BIOPHYS J, V74, P1533, DOI 10.1016/S0006-3495(98)77865-8 VARO G, 1983, BIOPHYS J, V43, P47, DOI 10.1016/S0006-3495(83)84322-7 Walther M, 2000, CHEM PHYS LETT, V332, P389, DOI 10.1016/S0009-2614(00)01271-9 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WEIDLICH T, 1987, BIOPOLYMERS, V26, P439, DOI 10.1002/bip.360260310 WEIDLICH T, 1988, J PHYS CHEM-US, V92, P6475 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 Woolard DL, 1997, J APPL TOXICOL, V17, P243, DOI 10.1002/(SICI)1099-1263(199707)17:4<243::AID-JAT436>3.0.CO;2-6 Xie AH, 2002, PHYS REV LETT, V88, DOI 10.1103/PhysRevLett.88.018102 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Whitmire, SE Wolpert, D Markelz, AG Hillebrecht, JR Galan, J Birge, RR Markelz, Andrea/0000-0003-0443-4319 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01 GM034548, R01 GM034548-15] Funding Source: Medline 122 3 31 Cell press Cambridge 1542-0086
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy